2009
DOI: 10.1037/a0015406
|View full text |Cite
|
Sign up to set email alerts
|

Testing a social-cognitive model of moral behavior: The interactive influence of situations and moral identity centrality.

Abstract: This article proposes and tests a social-cognitive framework for examining the joint influence of situational factors and the centrality of moral identity on moral intentions and behaviors. The authors hypothesized that if a situational factor increases the current accessibility of moral identity within the working self-concept, then it strengthens the motivation to act morally. In contrast, if a situational factor decreases the current accessibility of moral identity, then it weakens the motivation to act mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
782
5
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 739 publications
(840 citation statements)
references
References 79 publications
(165 reference statements)
31
782
5
22
Order By: Relevance
“…Within negotiations, relationship-promoting and self-promoting outcomes are often inversely correlated (Curhan, Neale, Ross, & Rosencranz-Engelmann, 2008). Further supporting these ideas, Aquino et al (2009) showed that providing a performance-based financial incentive increased the use of deception in a negotiation for those with strong (but not weak) moral iden-tities by temporarily decreasing the salience of moral identity relative to other identities.…”
Section: Explaining When Gender Differences In Negotiator Ethics Emergementioning
confidence: 52%
See 4 more Smart Citations
“…Within negotiations, relationship-promoting and self-promoting outcomes are often inversely correlated (Curhan, Neale, Ross, & Rosencranz-Engelmann, 2008). Further supporting these ideas, Aquino et al (2009) showed that providing a performance-based financial incentive increased the use of deception in a negotiation for those with strong (but not weak) moral iden-tities by temporarily decreasing the salience of moral identity relative to other identities.…”
Section: Explaining When Gender Differences In Negotiator Ethics Emergementioning
confidence: 52%
“…The negotiation lasted 15 min. Consistent with Aquino et al (2009), we included only those who held the role of manager (n = 112, 66 women) in our analyses in order to explore their deceptive behavior.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations